PENGARUH INTENSITAS MORAL TERHADAP PENGAMBILAN KEPUTUSAN ETIS DALAM PENGGUNAAN PERANGKAT LUNAK BAJAKAN - Suryanto Suryanto (Cakrawala - Jurnal Humaniora, 2011)
Piracy of information technology (IT) sotfware has been particularly detrimental to the softwareindustry billions of dollars per year. According to data from the Business Software Alliance (BSA)which has conducted studies around the world, during 2010 the last level of use of piratedbusiness software applications reached 42 percent worldwide (BSA 2010). If converted into cash,the total losses reach 59 billion dollars, an increase of 14% compared to 2009. And the BSAbelieves one reason piracy is so widespread is that many users of pirated software do not reallyunderstand that they act unethically. This paper investigates critical issues on ethical behavior,specifically the effects of moral intensity with ethical decision making in software piracy. In thisstudy, data were collected using a questionnaire based on two scenarios contain about ethicalissues in the use of software. Both scenarios related to software (1) users with a software licenseon multiple computers (1) hijacked on licenses that have not been paid. 340 samples of students inAMIK BSI, the 195 students in the class of Information Management, 100 students in the class ofComputer Engineering, and 45 student workers and professional software users already know theethics of the use of information technology. Regression analysis with SPSS program used to testthe hypothesis. This study shows that the moral intensity of individuals influence behaviorintentions in a situation-specific negatively associated with the ethical use of software for allscenarios.Keywords: Ethical, Decision Making, Software Piracy